China’s Model of Managing the Financial System - Brunnermeier, Markus K; Sockin, Michael; Xiong, Wei (Review of Economic Studies, 2022)
China’s economic model involves regular and intensive government interventions in financial markets, while Western policymakers often refrain from substantial interventions outside crisis periods. We develop a theoretical framework to rationalize the approaches of both China and the West to managing the financial system as being optimal given the differences in their respective economies. In this framework, a government leans against trading of noise traders but at the expense of introducing policy noise to the market. Our welfare analysis shows that under certain underlying economic conditions, the optimal government policy induces a government-centric equilibrium, in which government intervention is so intensive that all investors choose to acquire private information about policy noise rather than fundamentals. This policy regime characterizes China’s approach with financial stability prioritized over other policy objectives.